La evaluación de la calidad en un nuevo planteo curricular. Facultad de Agronomía. UNLPam (Praxis Educativa, 2012)
La evaluación de la calidad en un nuevo planteo curricular. Facultad de Agronomía. UNLPam
Keywords: evaluación